Media and collective memory – the analysis of modern Slovenian media discourse about mass graves in Huda Jama - Bednarska, Katarzyna (Specialized Languages in Intercultural Communication, 2020)
This article analyzes media discourse and the collective memory of Slovenes regarding the period of World War II and several post-war years. On the basis of media reports about the tenth anniversary of the discovery of mass graves in Huda Jama, it will be presented how the World War II was inscribed in the collective memory of Slovenes and how war events cause ideological divisions of Slovenian society.